The economics of demand-led growth : challenging the supply-side vision of the long run - opk 14/3/18; Setterfield, Mark (Cheltenham ; Northampton, MA : E. Elgar, 2002)
A collection of specially written essays that develop and apply the theory of demand-led growth
Includes bibliographical references and index.
Keywords: Demand (Economic theory); Supply-side economics; Economics; Economic policy; Economic development; United States; United States